2020
DOI: 10.1177/0038026120946677
|View full text |Cite
|
Sign up to set email alerts
|

‘The student experience’ and the remaking of contemporary studenthood: A critical intervention

Abstract: ‘The student experience’ is a formulation that will be familiar to many reading this article; increasingly the term has come to stand in for an imprecise set of values and practices around higher education study. Despite the fuzziness that characterises its use, ‘student experience talk’ has gained traction in education policy and rankings, academic research, and amongst students themselves. After initially drawing from Raymond Williams to situate ‘the student experience’ as a keyword across policy, marketing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In current research, I am applying a keywords-as-method approach to explore the competing uses of the concept of ‘elites’ across left and right-wing forms of anti-elitist sentiment, examining how the concept offers a historically specific way of framing and shaping concerns about class, merit, hierarchy and inequality in capitalist societies (Moran, 2022). Finally, in a collaborative study of concept of ‘the student experience’ in British university contexts, a keywords-as-method analysis has revealed the concept to work as an aspirational membership category that encourages and obfuscates a market logic in contemporary student behaviours while also, through its reification in university policy, enabling the scramble for its attainment and management in an increasingly competitive and metrics-driven university sector (Pötschulat et al, 2020).…”
Section: ‘Abstract As Method’ In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In current research, I am applying a keywords-as-method approach to explore the competing uses of the concept of ‘elites’ across left and right-wing forms of anti-elitist sentiment, examining how the concept offers a historically specific way of framing and shaping concerns about class, merit, hierarchy and inequality in capitalist societies (Moran, 2022). Finally, in a collaborative study of concept of ‘the student experience’ in British university contexts, a keywords-as-method analysis has revealed the concept to work as an aspirational membership category that encourages and obfuscates a market logic in contemporary student behaviours while also, through its reification in university policy, enabling the scramble for its attainment and management in an increasingly competitive and metrics-driven university sector (Pötschulat et al, 2020).…”
Section: ‘Abstract As Method’ In Practicementioning
confidence: 99%
“…In this short essay, written to mark the centenary of Williams’s birth, I propose to return to and resurrect this cultural materialist orientation in order to develop more fulsomely what I have come to think of as ‘keywords-as-method’; that is, to explore how we might use the power of the keywords approach for a deep study of the relationship of linguistic to social change, without stopping at or being confined by a simple glossary of terms. In so doing, I will reflect upon my own work in which I develop this approach, including a focus on the keywords ‘identity’ (Moran, 2015, 2018, 2020) ‘student experience’ (Pötschulat et al, 2020) and ‘elites’ (Moran, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the use of the concept tends to be a political intervention, in view of its sociological inadequacy. They also point out that the use of the concept smuggles in a market logic that homogenizes the elements in which it could be composed [26]. We believe that not only a poorly focused market logic can homogenize the elements of the student's experience, but also any superficial approach to the concept.…”
Section: Rq1: What Is (Undegraduate) Sx?mentioning
confidence: 96%
“…It is important to mention that the experiences of students who transition to higher education turn out to be an important factor in terms of their learning outcomes and engagement [87]. As the experiences of first year students have such a significant impact on their perception and academic results, it is possible to explain the large number of studies focused on this group of students [26,61,77,78,88,89].…”
Section: Rq1: What Is (Undegraduate) Sx?mentioning
confidence: 99%
“…This particularly visible episode crystallised longer and deeper tensions between the actions and policy of higher education (HE) institutions, including in response to the Covid-19 pandemic; students’ own self-advocacy; and contested public narratives on student loneliness and mental health, already persistently commodified and euphemised under the banner of ‘student experience’ ( Pötschulat, et al, 2020 ). This paper explores these tensions through critical reflection on a piece of co-produced research on student loneliness which began in the autumn of 2019, culminated in a collective journalling project with 14 participants over nine weeks from May to July 2020, and had an ongoing legacy in terms of drawing out useable insights for the host university, which was also the funder.…”
Section: Introductionmentioning
confidence: 99%